Medical and Psychological Rehabilitation for Patients with Spinal Degenerative Joint Diseases Using the Whole-Body Extreme Air Cryotherapy - Panchenko, Oleg; Kabantseva, Anastasiіa (Problems of Cryobiology and Cryomedicine, 2022)
Here, we have studied the rehabilitation efficiency for patients with spinal degenerative joint diseases using the wholebody extreme air cryotherapy (WBEACT) according to our own technique. The assessment of pain intensity on visual-analogue scale upon completing the rehabilitation therapy showed the pain disappearance in 68.4% of patients, and its significant reduction in 31.6%; increased daily motor activity, and decreased restrictions during walking in 90.8% of cases; improved well-being in 35.7%; enhanced activity in 43.9%, and mood change in 38.8%. Each WBEACT session increased the muscle strength and endurance for both genders of patients, thus testifying to a stimulating effect of cryotherapy to human body. The WBEACT application for rehabilitation of patients with spinal degenerative joint diseases enabled to normalize the psycho-emotional state as quickly as possible and improve functional state of neuromuscular apparatus, i. e. to reduce the pain and muscle tonic syndromes, strengthen the muscular skeleton, and increase the range of motion and endurance while standing, sitting and walking. Probl Cryobiol Cryomed 2022; 32(3):226–235